2019
DOI: 10.15421/111871
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the temperature regime of the North Atlantic coastal zone as an indicator of changes in the system of thermohaline circulation

Abstract: The purpose of the article is to analyze dynamics of the temperature regime of the surface layer of the atmosphere in the coastal zone of the North Atlantic as an indicator of changes in the thermohaline circulation system. In carrying out the research, comparative-geographical and historical statistical methods of the analysis of meteorological series were used. For research, 20 control points of the eastern part of the United States and Western Europe, which are located along the flow course of the Gulf Stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Research results (Wang, Chen, & Liu, 2015), conducted in China indicated a positive correlation between the reduction of the Arctic sea ice area and the increase in the number of foggy days in the country. Taking into account further reduction of the ice cover due to global warming [Maksymenko, Medvedeva, & Cherkashyna, 2019], a tendency to increase in the number of days with favourable conditions for the formation of smogs becomes a significant factor in increasing the level of environmental hazard in the region.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%
“…Research results (Wang, Chen, & Liu, 2015), conducted in China indicated a positive correlation between the reduction of the Arctic sea ice area and the increase in the number of foggy days in the country. Taking into account further reduction of the ice cover due to global warming [Maksymenko, Medvedeva, & Cherkashyna, 2019], a tendency to increase in the number of days with favourable conditions for the formation of smogs becomes a significant factor in increasing the level of environmental hazard in the region.…”
Section: Analysis Of Recent Research and Publicationsmentioning
confidence: 99%
“…A decrease in precipitation leads to a decrease in the yield of agricultural crops, in the mass of glaciers, etc. All this makes it relevant to assess climate change both on a global and regional scale (Cheung et al 2008;Chakrabordy et al 2013;Maksymenko et al 2018).…”
Section: Introductionmentioning
confidence: 99%